2009
DOI: 10.1007/s11671-009-9480-x
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Green Synthesis and Bioapplication ofl-Arginine-Capped Superparamagnetic Fe3O4 Nanoparticles

Abstract: Water-solublel-arginine-capped Fe3O4 nanoparticles were synthesized using a one-pot and green method. Nontoxic, renewable and inexpensive reagents including FeCl3,l-arginine, glycerol and water were chosen as raw materials. Fe3O4 nanoparticles show different dispersive states in acidic and alkaline solutions for the two distinct forms of surface bindingl-arginine. Powder X-ray diffraction and X-ray photoelectron spectroscopy were used to identify the structure of Fe3O4 nanocrystals. The products behave like su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 40 publications
(16 reference statements)
3
26
0
Order By: Relevance
“…All studies were carried out in triplicate. The saline solution used for this study was prepared by taking 0.9% NaCl, pH was adjusted to pH = 7.4 [28]. The % thrombosis and % hemolysis tests were performed as described elsewhere [29].…”
Section: Thrombogenicity and Hemolytic Potential Studymentioning
confidence: 99%
“…All studies were carried out in triplicate. The saline solution used for this study was prepared by taking 0.9% NaCl, pH was adjusted to pH = 7.4 [28]. The % thrombosis and % hemolysis tests were performed as described elsewhere [29].…”
Section: Thrombogenicity and Hemolytic Potential Studymentioning
confidence: 99%
“…All studies were carried out in triplicate. The phosphate buffered saline solution (PBS) used for this study was prepared by taking 138 mM NaCl, 1.5 mM KH 2 PO 4 , 8 mM Na 2 HPO 4 ·H 2 O and 2.7 mM KCl and pH was adjusted to pH = 7.4 (Lai et al, 2010).…”
Section: Blood Compatibility Of Irradiated Pva/ Cs Membranes Containimentioning
confidence: 99%
“…The phosphate buffered saline solution (PBS) used to study material-blood interactions are prepared by using the method reported elsewhere [33].…”
Section: Blood Compatibilitymentioning
confidence: 99%